Blockchain Technology and Social Policy Transformation: A Critical Examination and Recommendations - Nurten Ebru Özdemir; Gökçe Cerev; Doğa Başar Sarıipek; Salih Tosun (Sosyal Siyaset Konferansları Dergisi)
In recent years, Blockchain technology has emerged as a transformative innovation with significant implications on both a global and local scale. Its potential to revolutionise social policy in Turkey is profound and offers avenues for the development of transparent, reliable and participatory systems. As the concept of work evolves, traditional social protection and security systems rooted in conventional employment models must adapt to this changing landscape. In an era prioritising citizenship ties, the importance of financial stability and efficiency has never been greater, necessitating the formulation of precise needs-based social protection policies. Through its ability to enhance the accuracy of identifying individuals in need, the blockchain holds the promise of optimising resource allocation and facilitating the effective implementation of needs-based social policies. This study seeks to delve into the transformative potential of Blockchain technology within social policy systems in Turkey, with a specific focus on social assistance practices, and to provide recommendations for its integration. The significance of this study lies in its exploration of Blockchain’s decentralised digital structure of the blockchain, which ensures data integrity and is pivotal in establishing fair and transparent social assistance mechanisms. By pioneering research in this area, this study aims to bridge existing gaps in the literature and contribute to a deeper understanding of Blockchain’s impact on social assistance in Turkey. Methodologically, the study will start with an exhaustive review of the relevant literature to establish a robust conceptual and theoretical framework. Subsequently, the collected data will undergo descriptive analysis to provide comprehensive interpretation and reporting. In conclusion, the findings of this study affirm the unique benefits that Blockchain technology offers to the social policy system in Turkey, including increased efficiency, equity, and transparency within social assistance systems. By addressing implementation challenges, Blockchain can be tailored to suit the needs of social assistance programs, providing invaluable support to policymakers and decision-makers in shaping future policies. The integration of Blockchain technologies not only facilitates efficient resource allocation but also enables timely and accurate responses to social protection needs. Ultimately, it enables the simultaneous implementation of a rights-based, needs-driven social policy model, thus paving the way for transformative changes in social welfare systems.